PhET Simulation Media Part Time Using a Problem Based Learning Model Improves Student Learning Outcomes - Masfaratna; Ahmad Rosadi (Jurnal Pendidikan Profesi Guru, 2023)
Quantum physics is the science that deals with objects that are so small that they cannot be seen with the naked eye. Quantum physics is the study of the behavior of matter and energy related to the molecular, atomic, nuclear, microscopic levels, also in terms of security levels. Therefore, relevant media are needed to convey material about the half-life of an atom according to the independent curriculum through a scientific approach. One of the media related to this article is PhET simulation. This study used the Classroom Action Research (PTK) research method which was carried out in Class XII IPA1 to overcome the problems faced in class. This study uses observation, tests and documentation. In the examination results based on each cycle, it can be seen that the results of Cycle I and Cycle II showed a significant increase. After studying and analyzing the results, in the first cycle, the average student achievement data was 70.18, while in the second cycle, the average student achievement in the second cycle was 77.03. Learning related to management also increased from 55.56% in cycle I to 85.18% in cycle II. The completion rate increased from 55.56% in Cycle I to 85.18% in Cycle II. The results showed that the Problem Based Learning Model assisted by the Phet virtual laboratory could improve student learning outcomes on part-time material at MAN 1 Bungo.